Case of coeliac disease presenting in the psychiatry ward. (21st December 2016) - Oliveira-Maia, Albino J; Andrade, Isabel; Barahona-Corrêa, J Bernardo
Abstract : We describe a case of coeliac disease that was diagnosed in the psychiatry inpatient unit of a general hospital. The patient was admitted due to suicidal behaviours and developed an agitated catatonic state while in the inpatient psychiatry unit. An extensive diagnostic study allowed for the diagnosis of coeliac disease and while her state was unresponsive to antidepressants, anxiolytics, antipsychotics and electroconvulsive therapy, the patient improved significantly when a gluten-free diet was started. While it is well known that, occasionally, gluten sensitivity and coeliac disease can present as brain gluten sensitivity, such cases are typically characterised by motor and/or cognitive symptoms and by white matter abnormalities. Psychiatric presentations of these conditions have only rarely been reported.